Avenues for Repositioning the Academic Libraries in India - Patkar, Vivek (Journal of Information and Knowledge, 2010)
Academic scene in India is set to change considerably on three accounts namely, large-scale promotion of distance education mode, increasing privatisation of higher education and advances in information and communication technology (ICT). It is imperative that the traditional supporting system like the academic library will be required to reshape itself due to such makeover in learning, teaching and scholarly communication processes. Designing new services and their customised delivery by library to the remote users, for example, will play a major role in this context. Adopting and harnessing the ICT for this purpose is critical. To that end a review of select projections regarding academics and library is first made here. A few noteworthy initiatives for introducing new library practices are next described. Future operating environment for the Indian academic libraries is assessed and preparatory actions are outlined for repositioning these libraries to round off the paper.